Islamic economics and COVID-19 : the economic, social and scientific consequences of a global pandemic - Choudhury, Masudul Alam, 1948- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book is a timely exploration of an unprecedented, cataclysmic pandemic episode. It examines certain critical aspects of socio-scientific theory across a variety of diverse themes, and through an epistemic lens. The book investigates the general theory of pandemic episodes and their adverse long-term effects on human and environmental wellbeing. It includes an in-depth study of COVID-19 but also looks to the future to contemplate potential pandemics to come. The existing approach to the study of pandemics is critically examined in terms of the prevalent isolated and thus mutated way of viewing human and mechanical relations in the name of specialization and modernity. The book presents a novel model of science-economy-society moral inclusiveness that forms a distinctive theoretical approach to the issue of normalizing all forms of pandemic challenges. It is methodologically different from existing economic theory, including the critical study of microeconomic foundations of macroeconomics. Human and environmental existence along with its multidisciplinary outlook of unity of knowledge between modernity, traditionalism, and socio-cultural values is emphasized in the treatment and cure of pandemic episodes. The book is a unique reference work, offering fresh wisdom within the moral methodological worldview"--
The socio-scientific development outlook for global future -- Pandemic treatments for transforming cell mutation into normalcy in unity of knowledge as the ontological premise of technical modelling -- Wellbeing and sustainability : lessons from coronavirus episode in the light of Tawhidi unity of knowledge -- Normalizing pandemic episode by science-economy-society moral inclusiveness -- A generalized model of science-economy-society moral inclusiveness in complex pandemic regime -- The role of educational reform in COVID-19 normalization -- Selected reforms in business-pandemic studies to accord with the model of science-economy-society moral inclusiveness -- Conclusion: Future pandemic model beyond COVID-19.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: COVID-19 (Disease) -- Economic aspects; COVID-19 (Disease) -- Social aspects; COVID-19 (Disease) -- Epidemiology -- Methodology; Economics -- Religious aspects -- Islam -- Qurʼanic teaching; Economics -- Statistical methods; Economics -- Methodology; Epidemiology -- Mathematical models